1996
DOI: 10.1103/physrevlett.76.3428
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity of the Spin Structure Observed in the Optical Response of CeBi Single Crystals

Abstract: We report a study of the optical conductivity of CeBi in different magnetic phases. Going from the paramagnetic phase to the various antiferromagnetic and ferrimagnetic phases, different new interband transitions appear below the absorption edge of the p ! d transitions. These new interband transitions disappear in a magnetic field that is sufficiently strong to align the spins parallel. The appearance of new interband transitions is indubitably associated with the folding of the Brillouin zone, which is a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…the formation of magnetic superstructures leads to a folding of the valence and conduction bands and as a consequence to new interband transitions. Similar effects have also been observed recently in CeBi [6]. Because the latter material has a somewhat less complex magnetic phase 4 diagram with simpler antiferrornagnetic and ferrimagnetic phases a full schematic interpretation of the changes in the optical conductivity could be performed.…”
Section: The Effect Of Magnetic Superstructuressupporting
confidence: 75%
“…the formation of magnetic superstructures leads to a folding of the valence and conduction bands and as a consequence to new interband transitions. Similar effects have also been observed recently in CeBi [6]. Because the latter material has a somewhat less complex magnetic phase 4 diagram with simpler antiferrornagnetic and ferrimagnetic phases a full schematic interpretation of the changes in the optical conductivity could be performed.…”
Section: The Effect Of Magnetic Superstructuressupporting
confidence: 75%
“…1,5 CeAs, CeSb, and CeBi were reported to display an unusually large magnetooptical Kerr rotation. 3,4 Optical spectroscopy could prove that GdP is metallic, with a small number of free carriers derived from the Drude-type conductivity. 6 Similar metalliclike optical spectra were subsequently reported for a number of other rare-earth monopnictides, such as, e.g., LaSb, CeSb, PrSb, YbAs, and CeBi.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Pittini and coworkers pointed out that the electronic band structure is folded by the spin structure in the AF-1 phase. 10 As previously mentioned, the change in the σ(ω) spectrum can be explained by the band folding. However, the change in the σ(ω) spectrum between 11 and 25 K has never been previously observed.…”
Section: /9mentioning
confidence: 84%
“…9 Pittini and coworkers have indicated that the folding of the band structure of CeBi by the spin structure can be observed in the σ(ω) spectra. 10 Here, the spin moments originating from the Ce 4f 1 Γ 8 and σ(ω) spectra reflect the Bi 6p and Ce 5d band structure. The coupling between the Ce 4f 1 Γ 8 spin moment and the band structure is due to pf mixing.…”
mentioning
confidence: 91%